Early to medium term outcomes of osteochondral lesions of the talus treated by autologous matrix induced chondrogenesis (AMIC). Issue 2 (February 2021) - Ayyaswamy, Brijesh; Salim, Mohammad; Sidaginamale, Raghavendra; Elsayed, Mohammed; Karpe, Prasad; Limaye, Rajiv
Highlights: This is a retrospective study of functional outcome of AMIC procedure in patients with osteochondral injury of the talus. The mean diameter of the osteochondral lesion in our study is 1.7 cms. Our study has shown 88% success rate with AMIC procedure in osteochondral lesions of the talus irrespective of lesion size and age. AMIC procedure is a single stage cost effective cartilage regenerative procedure for lesion size more than 1.5 cms. Abstract: Background: The primary aim of the study is to evaluate the functional outcome following AMIC procedure in patients with osteochondral injury of the talus. The secondary aim is to evaluate if size of the lesion and patient's age influence outcome. Materials and methods: This is a retrospective study of 25 patients who underwent AMIC procedure of the talus treated by a single surgeon. Functional outcomes were evaluated using pre and post operative AOFAS and VAS scores. Results: The mean lesion size was 1.74 cms with 88% of lesions in the study more than 1.4 cms. There was a significant improvement in AOFAS score with mean improvement of 49.40 (p < 0.05) and VAS score of 5.36 (p < 0.05). We could not find any correlation between either age or lesion size with functional outcome for AMIC procedure. Conclusion: AMIC procedure seems to be a reliable treatment method for larger diameter osteochondral lesions of the talus up to 2.5 cms in diameter.